Determination of electrical parameters of individual multiwalled carbon nanotube using scanning probe microscopy techniques - D. V. Sokolov; N. A. Davletkildeev; I. A. Lobov (Омский научный вестник)
Based on the combination of conductive atomic force microscopy (C-AFM) and electrostatic force microscopy (EFM), the electrical parameters of undoped, nitrogen- and boron-doped individual multiwalled carbon nanotubes (CNTs) have been determined. The longitudinal electric resistance of CNTs is obtained using C-AFM. The determination of diameter, length and work function in CNT is based on the analysis of EFM data. Using two techniques of scanning probe microscopy, electrical conductivity, free carriers concentration, carriers mobility of individual multiwalled CNT are evaluated.